O congado (a) e a permanência do racismo na cidade de Uberlândia-MG: resistência negra, identidades, memórias, vivências (1978-2018) - Brasileiro, Jeremias (2019)
His research is inserted in the field of social history, with bias towards the popular culture associated to the cultural and religious manifestation denominated Congado or Congada. In this way, we aim to problematize issues inherent to this practice, without disregarding in these discussions, the historical process in which the subjects who are protagonists of this socio-cultural doing and living are socially involved. The central problem is to reflect on the permanence of racism and black resistance in the city of Uberlândia, which runs through social, cultural and religious relations, in leisure, work and power relationships, which are inserted in the respective manifestation. Among research support documents, stand out statutes and acts of religious brotherhoods, public documents, photographs, imagery resources derived from digital collections, which are composed of visual records available in different mediums of media, periodicals, electronic documents and other sources, including those from oral reports. In this respect, we make use of theoretical contributions that contribute to think about representations, temporalities, memories, modernities, transformations and cultural patrimonies. The proposed theme likewise runs through the understanding of the notions of identities and their complexities. It seeks to establish a relation between the tactics of experiences, as strategies to combat racism, through the cultural and religious manifestation of the Congado in the daily life of the congadeiros and in the days of the party of the Congada, when the racist practices appear of more accentuated and explicit way. It is also in this approach, to think of ancestry, connected to the present, a past that merges with modernity and points paths to the future, and thus to see this Afro-Brazilian manifestation of African descent, as a historical, social presence and cultural. In this bias, it is also this research, of the history of the city of Uberlândia, of which the black congener community is intrinsic part.